Implementation of Supplementary Feeding for Stunted Children - Hesti Putri Setianingsih; Endah Tri Wahyuni; Farah Lutfiah (Indonesian Journal of Early Childhood Education Studies, 2024)
The health problem that is currently a priority is stunting. Stunting is a nutritional problem that is still a health problem faced by the government. the method used in this study is a qualitative method with a descriptive approach. The purpose of this study was to describe the Implementation of Supplementary Feeding for Stunted Children in Lolu Village, Sigi Biromaru District, Sigi Regency. Data collection was carried out by observation, interviews, questionnaires, and documentation. The results of the study showed that: 25 children were found in the stunting category. The Implementation of Supplemental Feeding is carried out by providing additional food in the form of a complete menu that has been provided by cadres who work with several parties such as nutritionists, village midwives, and PKK mothers. After the provision of supplementary food, the stunting rate in Lolu Village, Sigi Biromaru District, Sigi Regency has decreased, this is because the distribution or distribution of PMT is carried out every day, with additional food that focuses on macronutrients and micronutrients aimed at improving the condition of children who are categorized as stunting.